2017
DOI: 10.1186/s12943-017-0722-8
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of lncRNA IGFBP4–1 reprograms energy metabolism to promote lung cancer progression

Abstract: BackgroundReprogrammed energy metabolism as an emerging hallmark of cancer has recently drawn special attention since it facilitate cell growth and proliferation. Recently, long noncoding RNAs (lncRNAs) have been served as key regulators implicated in tumor development and progression by promoting proliferation, invasion and metastasis. However, the associations of lncRNAs with cellular energy metabolism in lung cancer (LC) need to be clarified.MethodsHere, we conducted bioinformatics analysis and found insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
94
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 44 publications
0
94
0
2
Order By: Relevance
“…For example, lncRNA AKHE promotes tumor progression in hepatocellular carcinoma (HCC) via activation of NOTCH2 signaling [27]. Overexpression of lncRNA IGFBP4-1 reprograms energy metabolism to promote lung cancer (LC) cell proliferation and metastasis and inhibits apoptosis [28]. Similarly, lncRNA LINC01296 overexpression upregulates the expression of MYCN and promotes cell viability, migration, and invasion in human cholangiocarcinoma (CCA) cells [29].…”
Section: Discussionmentioning
confidence: 99%
“…For example, lncRNA AKHE promotes tumor progression in hepatocellular carcinoma (HCC) via activation of NOTCH2 signaling [27]. Overexpression of lncRNA IGFBP4-1 reprograms energy metabolism to promote lung cancer (LC) cell proliferation and metastasis and inhibits apoptosis [28]. Similarly, lncRNA LINC01296 overexpression upregulates the expression of MYCN and promotes cell viability, migration, and invasion in human cholangiocarcinoma (CCA) cells [29].…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanisms by which lncRNAs modulate glycolysis have also been documented. For instance, the lncRNA IGFBP4‐1 influences ATP production and expression of specific enzymes, including hexokinase 2 (HK2), pyruvate dehydrogenase kinase 1 (PDK1) and lactate dehydrogenase A (LDHA), and the aerobic glycolysis rate in lung cancer …”
Section: Lncrnas Involved In Energy Metabolismmentioning
confidence: 99%
“…Increasing evidence shows that lncRNAs play a critical role in cancer biology. Dysregulation of lncRNAs often serves as an independent predictor for poor prognosis of cancer patients . Our group has previously reported that circulating lncRNAs act as potential novel biomarkers for diagnosis and prognosis of non‐small cell lung cancer .…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of lncRNAs often serves as an independent predictor for poor prognosis of cancer patients. [5][6][7][8][9] Our group has previously reported that circulating lncRNAs act as potential novel biomarkers for diagnosis and prognosis of non-small cell lung cancer. 10 Several recent studies have focused on the involvement of lncRNAs in tumor metastasis because these lncRNAs have shown great promise in the discovery of new biomarkers for predicting prognosis in individual patients.…”
Section: Introductionmentioning
confidence: 99%